2017
DOI: 10.15252/embj.201696394
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of the FUS low‐complexity domain disrupts phase separation, aggregation, and toxicity

Abstract: Neuronal inclusions of aggregated RNA‐binding protein fused in sarcoma (FUS) are hallmarks of ALS and frontotemporal dementia subtypes. Intriguingly, FUS's nearly uncharged, aggregation‐prone, yeast prion‐like, low sequence‐complexity domain (LC) is known to be targeted for phosphorylation. Here we map in vitro and in‐cell phosphorylation sites across FUS LC. We show that both phosphorylation and phosphomimetic variants reduce its aggregation‐prone/prion‐like character, disrupting FUS phase separation in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

35
721
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 611 publications
(785 citation statements)
references
References 84 publications
(152 reference statements)
35
721
3
Order By: Relevance
“…Phosphorylation introduces negative charges into proteins and changes the charge distribution and the electrostatic interactions along the polypeptide backbone, and hence also the LLPS characteristics of proteins. For example, phosphorylation regulates LLPS of nephrine (Li et al , 2012), FUS (Monahan et al , 2017), and RNA binding protein CPEB4 (Guillén‐Boixet et al , 2016). Phosphorylation is also the major type of PTMs in tau (Morris et al , 2015), and more than 80 potential phosphorylation sites can be found in the amino acid sequence of tau (Reynolds et al , 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Phosphorylation introduces negative charges into proteins and changes the charge distribution and the electrostatic interactions along the polypeptide backbone, and hence also the LLPS characteristics of proteins. For example, phosphorylation regulates LLPS of nephrine (Li et al , 2012), FUS (Monahan et al , 2017), and RNA binding protein CPEB4 (Guillén‐Boixet et al , 2016). Phosphorylation is also the major type of PTMs in tau (Morris et al , 2015), and more than 80 potential phosphorylation sites can be found in the amino acid sequence of tau (Reynolds et al , 2008).…”
Section: Resultsmentioning
confidence: 99%
“…The range of sequence biases associated with IDRs that mediate phase separation indicates that there may be a range of underlying driving forces. These likely include electrostatic, dipole–dipole, pi–pi, cation–pi, hydrophobic, and hydrogen bonding interactions [9,49,50,5256] (Figure 2A,B). Indeed, mutational studies have demonstrated that phase separation of different LCDs can be prevented by interfering with a variety of residue types [9,10,14,16,57].…”
Section: Molecular Determinants Of Protein Phase Separation In Vitromentioning
confidence: 99%
“…Work from different labs has shown that both serine and tyrosine phosphorylation can control phase separation [12,52,89,90], and the same holds true for arginine methylation [49,91] and sumoylation [80]. Importantly, the activity of the dual specificity kinase DYRK3, which partitions into SG, was shown to be necessary for SG dissolution [92], suggesting that there might be specific cellular switches controlling these processes.…”
Section: Spatiotemporal Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Most amazingly, this mechanism offers the potential to generate conformational ensembles composed of enormous amounts of states for both liquid droplets and fibril structures, which are also extremely sensitive to various environmental factors such as pH and cellular processes, including phosphorylation of Ser, Thr and Tyr (Murray et al 2017;Monahan et al 2017;Shorter 2017). Therefore, it appears most likely that the biological functions of the prion-like domains request not just the formation of the liquid droplets but also the conformational dynamics, as well as further assembly into diverse fibril structures.…”
Section: Aggregation and Self-assembly Into Liquid Droplets And Fibrimentioning
confidence: 99%